Contraceptive use and mental health among women of reproductive age: insights from the Mozambique Demographic and Health Survey - Anaba. E.A.; Wright. M.E.; Alor. S.K.; et al. (BJPSYCH INTERNATIONAL, 2025)
Background Contraceptive use among women of reproductive age has increased significantly worldwide. However, little is known about contraceptive use and mental health among women in sub-Saharan African countries. Aims This study sought to investigate contraceptive use and self-reported measures of depression and anxiety symptoms among reproductive-age women in Mozambique using the most recent national data. Method Thestudyusedsecondarydatafromthe 2022–2023 Demographic and Health Survey of Mozambique.Atotalof6910(weighted)sexually active women aged15–49yearswereincluded in this analysis. Anxiety and depression scores were measuredusingself-reportquestionnaires.Linear regression analysis was conducted to assess the associations between depression and anxiety and contraceptive use. Results The prevalence of contraceptive use was 36.41%. About half of the hormonal contraceptive users (49.38%) were using injectables and 25.99% were using implants. In total, 9.14 and 2.83% of the women had moderate or high scores of self-reported anxiety respectively. Additionally, 5.24 and 5.42% reported moderate or high scores of depressive symptoms respectively. The use of hormonal contraceptives decreased anxiety symptoms by 0.47 units (β =−0.47; 95% CI −0.75 to −0.18; P<0.001) compared with no contraceptive use. The use of hormonal contraceptives decreased depressive symptoms by 0.75 units (β=−0.75; 95%CI−1.11to−0.39;P<0.001)comparedwith no contraceptive use. Conclusions This study has demonstrated a naturalistic association between contraceptive use, particularly hormonal contraceptives, and decreased anxiety and depression among Mozambican women of reproductive age. This likely reflects a complex, bi-directional relationship, the nature and mechanism of which should be investigated in further experimental research.
Research Article
Keywords: Contraceptive use; mental health; Mozambique